A low-profile antenna with parasitic elements and a DGS-based partial ground plane for 5G/WMAN applications - Liton Chandra Paul (16416966) (2024)
A low-profile antenna with three parasitic elements is designed and presented for fifth-generation (5G) and wireless metropolitan area network (WMAN) applications. This prototype covers the frequency range of 2.75–4.94 GHz, which is applicable for the lower 5G (3.33–4.2 GHz), WWAN n48 CBRS (US) (3.55–3.7 GHz), WiMAX rel 2 (3.4–3.6 GHz), n77 (3.3–4.2 GHz, most European and Asian countries), n78 (3.3–3.8 GHz, USA), and n79 (4.4–5.0 GHz, China, Hong Kong, Japan, and Russia) bands. The prototype is made of a low-loss, commercially available substrate material known as Rogers RT 5880 (εr = 2.2, tanδ = 0.0009) with a thickness of 0.79 mm. The optimized dimension of the proposed antenna is 35 × 25 × 0.79 mm3 (i.e., 691.25 mm3). The proposed 10-element array antenna is fed by a 50 Ω feeder. The maximum gain and directivity of the prototype antenna are 4.3 dB and 4.75 dBi, respectively. The radiation efficiency of the prototype varies from 86.79 to 92.14% (simulated) and from 86.23 to 91.48% (measured), and it is 89.48% (simulated) and 90.59% (measured) at 3.225 GHz. The impedance profile of the proposed 10-element array is (49.80-j1.72) Ω, which ensures good impedance matching. The VSWR and surface current of the low-profile antenna are 1.036 and 107.931 A/m at the center frequency of 3.225 GHz, respectively. The value of the scattering parameter (S11) is − 36 dB at the resonant frequency. By using a DGS-based partial ground plane and parasitic elements, it enhances bandwidth to 2.19 GHz. Therefore, the tested prototype is an excellent candidate to be deployed for 5G/WMAN applications with respect to the different presented parametric studies. Other Information Published in: Discover Applied Sciences License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42452-024-05669-9